تجلّيات التشكيل الإبداعي في قصيدة (عائشة والعقرب) لعبد الرّحمن أخذاري ــــ مقاربة أسلوبية - حاجي عبد العزيز; نقبيل عبد العزيز (University of Eloued جامعة الوادي, 2025)
ملخّص: في خضمِّ التحوّلات التي شهدها الخطاب الشعري العربي الحديث، غدت الأسلوبية أفُقًا قرائيًا لا غنى عنه لاستكشاف البنى الداخلية للنصوص، وتحليل طرائق اشتغالها الجمالي والدلالي. وفي هذا الإطار تتنزّل هذه الورقة البحثية التي تتوخّى مقاربة قصيدة (عائشة والعقرب) لعبد الرحمن أخذاري من منظور أسلوبي، وذلك في محاولة لاستجلاء مظاهر التشكيل الإبداعي عبر المستويات الآتية: الإيقاع، التركيب، الدلالة، والبلاغة. في مسعى يهدف إلى الكشف عن العلاقة بين هذه المكوّنات الأسلوبية، وبين تجربة الشاعر في صياغة رؤية فنية تعكس تجربة إنسانية ذات أبعاد وجدانية ومجتمعية عميقة. Abstract: Amid the transformations experienced by modern Arabic poetic discourse, stylistics has emerged as an indispensable interpretive horizon for exploring the internal structures of texts and analyzing their aesthetic and semantic mechanisms. Within this framework, the present paper seeks to approach the poem "Aisha and the Scorpion" by Abdelrahman Akhdari from a stylistic perspective, in an attempt to elucidate the manifestations of creative formation across the following levels: rhythm, syntax, semantics, and rhetoric. This endeavor, with the aim of uncovering the relationship between these stylistic components and the poet’s experience, seeks to craft an artistic vision that reflects a profoundly human experience with emotional and societal dimensions.
مقال . القارئ للدراسات الأدبية و النقدية و اللغوية. مج 08. ع 02
Keywords: الأسلوبية، البناء الإيقاعي، التشكيل التركيبي، التوتر الدلالي، المفارقة البلاغية.; Key words: stylistics; rhythmic structure; syntactic formation; semantic tension; rhetorical paradox.